2016
DOI: 10.1176/appi.ps.201500058
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Individualized Placement and Support Principles Into Vocational Rehabilitation for Formerly Incarcerated Veterans

Abstract: Incorporating many of the principles and techniques of IPS into an existing vocational program was associated with improved employment outcomes over the six-month follow-up period and should be considered a viable rehabilitation option when working with this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
(16 reference statements)
1
22
0
Order By: Relevance
“…Studies include trials from Asia (Japan, Mainland China, Hong Kong), Australia, North America (Canada and the United States) central and northern Europe (Italy, Switzerland, Germany, Netherlands, Norway, Sweden, Denmark and the United Kingdom) and Eastern Europe (Bulgaria) (Table ). We excluded two studies from Scandinavia, and one from the United States that used a modified version of IPS with patients with moderate mental illness and substance abuse . One Norwegian study with enhanced IPS and no fidelity report were excluded , and we also excluded one randomized trial performed at a methadone clinic in the United States , with primarily opioid use disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Studies include trials from Asia (Japan, Mainland China, Hong Kong), Australia, North America (Canada and the United States) central and northern Europe (Italy, Switzerland, Germany, Netherlands, Norway, Sweden, Denmark and the United Kingdom) and Eastern Europe (Bulgaria) (Table ). We excluded two studies from Scandinavia, and one from the United States that used a modified version of IPS with patients with moderate mental illness and substance abuse . One Norwegian study with enhanced IPS and no fidelity report were excluded , and we also excluded one randomized trial performed at a methadone clinic in the United States , with primarily opioid use disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Vocational training was the most commonly studied psychosocial factor in relation to the health of justice-involved veterans. The majority of studies were randomized controlled trials comparing vocational training to usual care among justice-involved veterans in VHA settings (LePage et al, 2016, 2017; LePage, Lewis, Washington, Davis, & Glasgow, 2013; LePage, Ottomanelli, Barnett, & Njoh, 2014; LePage, Washington, Lewis, Johnson, & Garcia-Rea, 2011). Screening for psychosocial issues in primary care was addressed by two studies (Bikson, McGuire, Blue-Howells, & Seldin-Sommer, 2009; Cook, Freedman, Freedman, Arick, & Miller, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…95,114 Six studies, including a number of observational studies that were highly rigorous, reported the advantages of employer buy-in and incentives to take on individuals with health concerns as a means of reducing barriers to entering the workforce. [60][61][62]64,95,114 Five studies described how employers provided accommodation to employees, such as individualizing schedules. 44,52,64,106,114…”
Section: Intervention Team Work With and Engages Employersmentioning
confidence: 99%
“…[60][61][62]64,95,114 Five studies described how employers provided accommodation to employees, such as individualizing schedules. 44,52,64,106,114…”
Section: Intervention Team Work With and Engages Employersmentioning
confidence: 99%